To solve the equation \( 0 = -13x(x - 6) \), we first set the factored form equal to zero:
\[ -13x(x - 6) = 0 \]
This equation will be true if either factor is equal to zero:
-
Set the first factor to zero: \[ -13x = 0 \quad \Rightarrow \quad x = 0 \]
-
Set the second factor to zero: \[ x - 6 = 0 \quad \Rightarrow \quad x = 6 \]
Thus, the solutions to the equation are:
\[ x = 0 \quad \text{and} \quad x = 6 \]
The solution set can be expressed as:
\[ x = {0, 6} \]
Therefore, the correct response is:
The solution set is \( x = {0, 6} \).